Mobile Technologies in the Process of Teaching Music Theory - Goncharova, M.S. (2020)
The article provides teaching materials on the use of mobile technologies in the music-theoretical courses of children’s art schools. The use of mobile technologies allows teachers to organize their teaching activities (create a portfolio or a website), create an environment for remote support for learners (virtual classroom with assignments, tests, etc.), change the principles of classwork and homework by means of mobile applications and by making training programs personal and individual, adapted to the needs of each student. Tablets and gadgets have always attracted children, therefore, these familiar devices and the element of game and competition (various music applications) can help music-theoretical courses become much more interesting, draw children’s attention and energize them.